“Mãe solo é mãe sozinha”: tecendo vivências de mães negras em Fortaleza-CE e região metropolitana - Lima, Taiane Alves de (2021)
The exercise of writing this dissertation is born from an effort to reflect on what it is be a single mother through the life trajectory of black women, living in the city Fortaleza (CE) and the Metropolitan Region. In the quest to build a black femin anthropology, from the perspective of a daughter of a single mother, I seek understand the intersectionality between mothering, affectivity and loneliness of bla women. In this way, this work's methodology is an ethnographic research guided the intersectional analysis of these women's narratives. The objective is to understan the everyday symbols and meanings of motherhood, in order to understand the da trajectories that involve the solo mothering of black women throughout their experien related to individual and collective issues that structure intersectional oppressions.